2017
DOI: 10.1186/s13068-017-0868-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and key genes expression related to carbon fixation pathways in Chlorella PY-ZU1 cells and their growth under high concentrations of CO2

Abstract: BackgroundThe biomass yield of Chlorella PY-ZU1 drastically increased when cultivated under high CO2 condition compared with that cultivated under air condition. However, less attention has been given to the microalgae photosynthetic mechanisms response to different CO2 concentrations. The genetic reasons for the higher growth rate, CO2 fixation rate, and photosynthetic efficiency of microalgal cells under higher CO2 concentration have not been clearly defined yet.ResultsIn this study, the Illumina sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Carbonic anhydrase (CA) and Rubisco are two key enzymes in the microalgae CO 2 concentrated mechanism (CCM) and play important roles in carbon transport and metabolism [34]. Therefore, the enzyme activity of CA and Rubisco was determined to characterize the effect of culture conditions on their CO 2 fixation process.…”
Section: Carbonic Anhydrase and Rubisco Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonic anhydrase (CA) and Rubisco are two key enzymes in the microalgae CO 2 concentrated mechanism (CCM) and play important roles in carbon transport and metabolism [34]. Therefore, the enzyme activity of CA and Rubisco was determined to characterize the effect of culture conditions on their CO 2 fixation process.…”
Section: Carbonic Anhydrase and Rubisco Activity Assaymentioning
confidence: 99%
“…Most significantly, the transcript abundance of Rubisco (EC4.1.1.39) was down-regulated in the Calvin cycle, which catalyzes the carboxylation of ribulose 1,5-diphosphate with carbon dioxide in the Calvin cycle, and then is a key enzyme in the carbon concentrating mechanisms. In control group, the carbon source was insufficient and Chlorella need to activate the carbon concentrating mechanisms (CCM) to maintain normal cell growth [34,35]. But in the other three groups, there are enough carbon sources (CO 2 or acetic acids), the algae do not need to activate CCM, and therefore resulted in the down-regulation of Rubisco.…”
Section: Transcriptome Analysismentioning
confidence: 99%
“…It showed that a high CO 2 level stimulated lipid accumulation in microalgae in both light and darkness. High CO 2 level is considered a stress condition to promote lipid accumulation for some algae species [3, 31]. The other possible explanation is that lower O 2 partial pressure in higher CO 2 mixtures lowers the DO in the broths, which is lethal to algal cells [1] and eventually decreases the lipid content in microalgae cells [32].…”
Section: Resultsmentioning
confidence: 99%
“…Most of enzymes, such as phosphoribulokinase (PRK), phosphoglyceratekinase (PGK), RuBP carboxylase (rubisco), fructose‐bisphosphatase aldolase (ALDO), and glyceraldehyde phosphate dehydrogenase (GAPDH), plays an important role in the carbon fixation process (Huang et al, 2017; Silveira & Carvalho, 2016). Many DEGs, such as rbcL , PGK , GAPDH , and ALDO , were upregulated, which might enhance carbon synthesis in S .…”
Section: Discussionmentioning
confidence: 99%